The Representation of Social Class in the Illustration of Sketches by Boz by Dickens - Nurul Imansari (Hasanuddin University, 2020)
The study object in this research is the representation of social class in the illustration of Sketches by Boz by Charles Dickens (1895). Social class is one of the most prominent themes raised by Charles Dickens in his work to satirize the condition of Victorian England as a form of empathy towards the lower class people. Dickens tries to portray that phenomenon into a series of story and illustration of people’s everyday life in his work ‘Sketches by Boz’. However, this social phenomenon is always depicted and discussed mostly in term of the narration form. On the contrary, illustration is often being ignored. The aim of this study is to bring together the importance of illustration in its relationship to the text. The method used in this study was a descriptive qualitative. It will examine how social class is portrayed in the illustration of Dickens’ Sketches by Boz by focusing particularly on the variety of techniques used by the illustrators in producing the illustrations. The result shows that both narration and illustration highlights the social class reality in the Victorian era. The narration and the illustration cannot be separated in Charles Dickens’ Sketches by Boz since it is created to be a description of people’s everyday life in Victorian London. Keywords: Charles Dickens, Illustration, Narration, Social Class